Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M189/2 - Steffen Ziegler; Stefan Kinne; Mia Schumacher; Anne-Cathrin Wölfl (PANGAEA, 2023)
During M189/2 that took place in the Atlantic between 2023-05-16 and 2023-06-04, multibeam bathymetry raw data were recorded using the vessel extquotesingles built-in Kongsberg EM122 echosounder. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data (zip file) and the cruise report for details.